MENGUKUHKAN METODE ‘URF KELOMPOK DALAM MELANGGENGKAN KEBERAGAMAAN UNTUK PENENTUAN BULAN QAMARIYAH TAREQAT SYATTHARIYYAH DI SUMATERA BARAT - Tarihoran, Adlan Sanur (Alhurriyah, 2016)
Tareqat Syatthariyah has long grown and developed in Minangkabau, along with the entry of Islam into Minangkabau. One of developed local ‘urf and still survive and sustainable even become an annual event and habits of the fellow Syatthariyah worshipers is moon sighting ("maliek bulan") as one of the models in hisab science. This is in accordance with their 21 basic teachings for followers of tareqat Syatthariyah particularly in West Sumatra. In which to determine the initial entry of fasting month of Ramadan with "ru'yatul hilal". Crowded locations are in Koto Tuo Agam and Ulakan Padang Pariaman. This habits often make them fasting two days after the Government's decision and this become a different source of religious. This study was conducted to explore or probe about this group habit as well as the methods they did to "maliek bulan" or ru'yatul hilal. So it will get an idea about the reason why (undeniably) the existence of these activities carried out by followers of tareqat Syatthariyah in West Sumatra until now.